A brief history of the Chinese language. V, Middle Chinese lexicon 1 - Xiang, Xi (London : Routledge, 2023)
As the fifth volume of a multi-volume set on the Chinese language, this book studies the development of monosyllables and polysyllables in Middle Chinese and the overall evolution of lexical meanings during the period. Focusing on lexicons in Middle Chinese, the Chinese language used between the 4th and the 12th centuries CE, the book first introduces the monosyllabic neologisms of Middle Chinese, including characters and words derived from Old Chinese lexicons and those newly created. It then examines the development of polysyllabic words in Middle Chinese, ranging from single-morpheme words to tautologies and compound words. The final chapter discusses the changes and extension of word meanings in medieval Chinese. Illustrated with abundant examples, this comprehensive groundwork on Chinese lexical history will be a must-read for scholars and students studying ancient Chinese language and linguistics and especially for beginning learners of the Middle Chinese lexicon.
Keywords: Chinese language -- Middle Chinese, 1200-1919 -- Dictionaries -- English; Chinese language -- History